KOMUNIKASI LINTAS BUDAYA DI INSTITUSI PENDIDIKAN Studi Kasus: Perguruan Tinggi Mayoritas Mahasiswa Tionghoa dengan Pengajar Pribumi - Meilani Dhamayanti (Sociae Polites, 2014)
AbstractCommunication and culture have a reciprocalrelationship of mutual influence. In the daily life,communication and culture have a veryimportant role. In the educational institutionscommunication and culture are often touch toeach other therefore study on communicationand culture in the educational institution is veryneeded since the diversity of life itself. Thisresearch is using cross cultural communicationtheory and qualitative method to describe theresearch process. The research conclusion is thatit needs an active role of the lecturer so thatbarriers within the cross cultural communicationcan be solved. In other side it is also importantto have collaboration between students andlecturers to achieve the learning outcome.Key Words: Cross Cultural Communication,Educational InstitutionKeywords: Cross Cultural Communication,Educational Institution AbstrakKomunikasi dan budaya memiliki hubungantimbal balik yang saling mempengaruhi. Dalamkehidupan sehari-hari komunikasi dan budayamemiliki peranan yang sangat penting. Melaluiinstitusi pendidikan, komunikasi dan budayakerap bersinggungan. Karenanya kajiankomunikasi dan budaya di institusi pendidikansangat diperlukan mengingat kehidupansemakin beragam. Penelitian ini menggunakanteori komunikasi lintas budaya dan metodologikualitatif yang bertujuan untuk menggambarkanhasil penelitian. Adapun kesimpulan daripenelitian ini adalah diperlukan peran aktifdosen agar hambatan komunikasi lintas budayadalam institusi pendidikan bisa dihadapi. Di sisilain penting pula adanya kerjasama antaradosen dan mahasiswa agar tujuan pembelajarandapat tercapai.Kata Kunci: Komunikasi Lintas Budaya, IntitusiPendidikan